Comparative Study on Thresholding Techniques of Discrete Wavelet Transform (DWT) to De-noise Corrupted ECG Signals (International Journal of Engineering and Computer Science, 2014)
The electrocardiogram (ECG) signals which are recording of bioelectric potential caused by rhythmical activities are usually corrupted with various sources of noise. In this paper, Discrete Wavelet Transform (DWT) based technique is used to de-noise ECG signals. A comparative study is done on the soft and hard thresholding DWT for several ECG signals for different levels of signal to noise ratio (SNR). The SNR improvement (SNRimp) and Percent Root mean square Difference (PRD (%)) is analyzed. The results show that the soft-thresholding technique performs better than the hard-thresholding to de-noise ECG signal